Studying mutuality and perversity in the impacts of human resource management on societal well‐being: Advancing a pluralist agenda. (4th April 2021) - Boxall, Peter
Abstract: Situated within a societal perspective on human resource management (HRM), this paper asks how HRM academics can make a better contribution to understanding the impacts of HRM on societal well‐being. It argues that we should target the 'so what?' questions that matter to society, including important issues of employer–employee misalignment and of perverse alignment ('perverse‐performance work systems'). It calls for an approach to societal issues in HRM that is problem‐focused and theory‐informed. While recognising some validity to the criticisms of academic HRM raised in the 'psychologisation' debate, the article argues that the critique is over‐generalised and contests the idea that the concern of HRM academics with enhancing workplace mutuality is an expression of a unitarist ideology. Mutuality and unitarism should not be conflated. In advancing a pluralist agenda, it argues that we must become better at theoretical integration, at synergising our research methods and at engaging constructively with practitioners and policy makers.